Structure Design and Simulation of a Spherical Coupled Cervical Spine Rehabilitation Robot - Bao Cheng; Liu Fanghua; Cao Yongxin; Wang Zheng (Jixie chuandong)
Aiming at the problems of structure, volume, function and wearability of various cervical spine rehabilitation institutions at home and abroad, a spherical coupled cervical spine rehabilitation robot scheme is proposed. Firstly, starting from the common rehabilitation actions of patients with cervical spondylosis, a new type of spherical coupled mechanism is designed according to the physiological structure and kinematic mechanism of the human neck, aiming at better realizing the rehabilitation training of the head and neck of patients. The screw theory is used to analyze the degree of freedom of the mechanism, the kinematics and dynamics model of the robot is established, the solution formula and dynamic equation of the mechanism kinematics is obtained, and the movement space of the mechanism is obtained through Matlab simulation to verify that it meets the space requirements for rehabilitation training. The step function is written through the model action in Adams, and the curve obtained from the kinematics simulation is compared and analyzed with the theoretical calculation results. Finally, the transient dynamics analysis is performed on the key parts of the robot through Ansys Workbench, and the stress nephogram of the mechanism is obtained to verify the rationality of its structural design, which lays the foundation for prototype construction and control strategy research.